Research note: Petrobras privatization - Ferreira, Francismar Cunha (Geografares, 2020)
This note seeks to highlight the dimension of Petrobras' dismantling that has been intensified in the current context of neoliberal policies in Brazil. In this sense, it identifies, locates and maps all the assets of the different segments (production, distribution, transport and refining) who were sold and who have the sale announced by Petrobras. This work was carried out through analysis of Petrobras' administrative reports, newspaper reports, statistical data from the National Petroleum Agency (ANP). It was possible to conclude that Petrobras is currently undergoing a huge dismantling. This has intensified since the 2015 coup when the company's management stopped thinking of it as an integrated energy company and simply started to slice it into several offers to the private sector.
Keywords: Petrobras; Privatization; Petroleum; Gas